Predictors and outcome of emergent Liver transplantation for patients with acute-on-chronic liver failure. Issue 8 (August 2021) - Kim, Ji Eun; Sinn, Dong Hyun; Choi, Gyu-Seong; Kim, Jong Man; Joh, Jae-Won; Kang, Wonseok; Gwak, Geum-Youn; Paik, Yong-Han; Choi, Moon Seok; Lee, Joon Hyeok; Koh, Kwang Cheol; Paik, Seung Woon
Abstract: Background and aims: Controversy exists over whether emergent liver transplantation (LT) should be performed for patients with acute-on-chronic liver failure (ACLF), especially for patients with multiple organ failure. Methods: A total of 110 ACLF patients, defined by the European Association for the Study of the Liver (EASL) Chronic Liver Failure-Sequential Organ Failure Assessment (CLIF-SOFA) criteria were analyzed. The primary outcome was overall survival after ACLF diagnosis. Results: During follow-up, 76 patients received LT (59 received deceased-donor LT and 17 patients received living-donor LT). The overall survival was better for patients who received LT than patients who did not (82.9% vs. 17.6%, P < 0. 001). Among the 76 patients who received LT, the overall survival was not different according to ACLF grade at diagnosis (70.0%, 85.3%, and 84.4% at one-year for ACLF grades 1, 2, and 3, respectively, P   =   0.45 ). The baseline model for end-stage liver disease (MELD) score and progression of the ACLF grade during the pre-transplant period were independent factors for survival after LT. The one-year survival rate was 92.3% for patients with baseline MELD scores of ≤ 32 without ACLF grade progression, whereas it was 33.3% for those with baseline MELD scores of > 32 and ACLF grade progression. Conclusions: Emergent LT provided a significant survival benefit to ACLF patients, regardless of the baseline ACLF grade. Post-LT outcomes were associated with baseline MELD scores and ACLF progression during the pre-transplant period, which might be used in the emergent LT plan for patients presenting with ACLF.